Design of experiments for generalized linear models - Russell, K. G. (Chapman & Hall/CRC interdisciplinary statistics, 2019)
While there are numerous books on the analysis of Generalized Linear Models (GLMs), there is very little information available on how to design the experiments that will collect the data. This book will describe the theory and methods for designing experiments to collect data that will be analysed by GLMs. It shows that the extensive theory underlying design for linear models does not work for GLMs, and gives practical guidance as to how best to design experiments for GLMs. It includes lots of examples to illustrate the topics, and is supplemented by R code for their implementation.